Citizenship in Islam: View of Imam Al-Ghazali - Wicaksono, Yudi Krisno; Aziz, Abd. (PT. Riset Press International, 2023)
As the role and function of the nation-state continue to expand, citizenship in the contemporary context has also developed. Islamic thoughts about being part of the political community, territory, and government system are all included in the data sources of the Al Quran and hadith. This study aims to discuss citizenship in Islam: the views of Imam Al-Ghazali. In this paper, researchers used the literature study method. In collecting data, the researcher uses literary research methods. This research was conducted by browsing and viewing literature and research related to library materials. These study results are related to the concept of citizenship in the analysis of Al-Ghazali's study, which is immovable in politics and law. A country must have a forward orientation and not continue with its dark past. A country and a government must organize themselves both from good citizens and a just government to achieve goals that are shared.